CCNA 200-301 exam cram - Sequeira, Anthony (Pearson, 2020)
Cisco CCNA 200-301 Exam Cram is the perfect study guide to help you pass the Cisco CCNA 200-301 exam, providing coverage and practice questions for every exam topic. The book contains an extensive set of preparation tools, including exam objectives, pre-assessments, topic overviews, Exam Alerts, Cram Savers, Cram Quizzes, chapter-ending practice questions, author notes and tips, and an expansive glossary. The book also contains the extremely useful Cram Sheet tear-out: a collection of essential facts and numbers in an easy-to-review format. Complementing all these great study tools is the powe.
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed September 18, 2020)
Keywords: Computer networks -- Study guides -- Management -- Examinations; Computer security -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Réseaux d'ordinateurs; Gestion; Examens; Guides de l'étudiant; Sécurité informatique; Examens; Guides de l'étudiant; Computer networks; Management; Examinations; Computer security; Examinations; Electronic data processing personnel; Certification; examination study guides; Study guides; Guides de l'étudiant